Nekaj več o praštevilih - Breznik, Kristijan (Matematika v šoli, 2012)
Prime numbers have a special place in mathematics and for that reason they have been very well researched. We present some well known problems, statements and conjectures related to prime numbers. Most of the problems are formulated in a simple way, but that doesn't mean that their solutions are simple.
Keywords: composite numbers; number theory; praštevila; prime numbers; sestavljena števila; teorija števil